PERSEPSI NASABAH TERHADAP PENERAPAN 7P DALAM PEMASARAN PRODUK KUR PT BANK RAKYAT INDONESIA (PERSERO) TBK.UNIT TOMOHON UTARA KOTA TOMOHON - Prisca Seyla Glady Tumewu; Joachim N.K. Dumais; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2017)
The objective of this research is to analyze the perception of consumers towards the implementation of the marketing 7P people KUR PT Bank Rakyat Indonesia (Persero) Tbk. Northen Tomohon Unit, Tomohon City by using the concept of a Likert Scale to analyze 7P (product, price, place, promotion, people, physical evidence and process). The research was conducted in October through December 2016, using primary and secondary data. Sampling technique using purposive sampling method and sample size is 88 respondents. The analitycal method used is descriptive data analysis to describe the perception customer towards the implementation of the program 7P KUR Bank Rakyat Indonesia Unit in northern city of Tomohon. To measure the perception was used Likert Scale. The results showed that the perception of customer satisfaction index score towards the delivery service kredit of the people in the bank BRI Nothen Tomohon Unit, Tomohon city is at its 84,41% and relatively strongly agree (SS).